Policy Strategy for Strengthening the Alignment between Corporate Social Responsibility (CSR) and the Regional Medium-Term Development Plan (RPJMD) of Medan City - Hendra Abdillah Lubis (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2026)
Regional development is confronted with increasingly complex social, economic, and environmental challenges, while the fiscal capacity of local governments through regional budgets remains limited. This condition necessitates the optimization of alternative resources, including Corporate Social Responsibility (CSR) programs from the private sector. In the context of Medan City, the Regional Medium-Term Development Plan (RPJMD) serves as a strategic instrument to guide integrated and sustainable development. However, the current implementation of CSR programs has not been fully aligned with the RPJMD, resulting in fragmented, uncoordinated initiatives that often overlap with government programs. The main issue identified is the low willingness of companies to report their CSR plans and realizations to the Medan City Government. This is primarily due to the absence of binding regulations that mandate CSR reporting at both national and local levels. Various efforts have been undertaken by the local government, including the implementation of CSR Awards, the establishment of a CSR Coordination Team, and the development of a centralized CSR digital platform. Nevertheless, these initiatives have not significantly improved corporate participation in reporting and aligning CSR programs. This study aims to formulate policy strategies to enhance the alignment between corporate CSR programs and the RPJMD of Medan City. The research employs a policy analysis approach combining qualitative and quantitative methods, utilizing literature review, interviews, and secondary data analysis from official statistics and regional planning documents. The findings are expected to provide policy recommendations that strengthen collaboration between the government and the private sector, ensuring that CSR implementation becomes more integrated, targeted, and capable of contributing optimally to sustainable regional development